2014
DOI: 10.1144/geochem2014-280
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive approach to understanding ore deposits using portable X-ray fluorescence (pXRF) data at the Plutonic Gold Mine, Western Australia

Abstract: Since 2009 all underground face samples and diamond-drill core samples at the Plutonic Gold Mine (Plutonic), Marymia Inlier, Western Australia have been analysed by portable X-ray fluorescence (pXRF) following a systematic approach. This method is rapid and cost-effective and provides analyses of a large suite of chemical elements which can be used to characterize lithology and alteration. The delivery of a comprehensive workflow for sample preparation, analysis, results correction, and rapid processing enable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…These commercial standard whole rock assays form a comparative data set for the pXRF analyses. Analyses of the same 58 samples were conducted using an Olympus Delta X Premium pXRF over three analytical runs at CODES-University of Tasmania following the methods outlined in Fisher et al (2014) and Gazley et al (2015) Each whole rock analysis from Northparkes was replicated using pXRF. Each sample was analysed as a rock/core sample and as a pulverised equivalent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These commercial standard whole rock assays form a comparative data set for the pXRF analyses. Analyses of the same 58 samples were conducted using an Olympus Delta X Premium pXRF over three analytical runs at CODES-University of Tasmania following the methods outlined in Fisher et al (2014) and Gazley et al (2015) Each whole rock analysis from Northparkes was replicated using pXRF. Each sample was analysed as a rock/core sample and as a pulverised equivalent.…”
Section: Discussionmentioning
confidence: 99%
“…A precise and accurate measure of Zr and Y (comparable to traditional assay methods) can be obtained using a systematic approach to pXRF analysis and data reduction (Fisher et al, 2014;Gazley et al, 2015;Wells et al, 2018;Ahmed et al, 2019). Using Zr/Y ratios with pXRF allows for rapid assessment of magmatic fertility in altered terranes.…”
Section: Introductionmentioning
confidence: 99%
“…This study has shown that the pXRF analysis has the potential to improve the understanding of stratigraphy and mineralization in the Mount Pleasant deposit area. The pXRF analysis gives geologists greater confidence in models than would have been possible without these data (Gazley et al, 2015). A comprehensive model for the evolution of the Mount Pleasant Caldera Complex was presented by McCutcheion (1990) based on the concept of a single caldera cycle.…”
Section: Potential Impact On Exploration Strategiesmentioning
confidence: 99%
“…이와 같은 p-XRF 장비는 측정 대상의 원소 함량을 정확 하게 분석하는 것이 아니라 형광 X선의 강도를 장치의 자 체적인 보정에 의해 변환시키기 때문에 정확도가 상대적으 로 떨어진다. 그러나 장비의 높은 효용성으로 인해 지난 수 십년간 지속적으로 개량되면서 검출 능력 또한 향상되고 있으며 정확성 확보를 위하여 측정값의 보정에 대한 연구 가 이루어지면서 p-XRF가 가지는 단점을 보완해나가고 있 다 (Fisher et al, 2014;Gazley et al, 2015;Lemière, 2018;Pang et al, 2022;Simandl et al, 2014;Suh et al, 2016;Le Vaillant et al, 2014). 이로 인해 특히 광물 탐사 및 채광시 품위관리를 위한 정량 분석에 중요한 장비로 점차 자리잡 는 추세이다 (Burnett et al, 2016;Durance et al, 2014;Fisher et al, 2014;Gazley et al, 2015;Hall et al, 2016;Pang et al, 2022;Quiniou and Laperche, 2014;Zou et al, 2022).…”
unclassified